Pattern of Ocular Findings in Patients with Biopsy-proven Sarcoidosis in Turkey. (2nd August 2013) - Sungur, Gulten; Hazirolan, Dicle; Bilgin, Gulden
Abstract: Purpose : To evaluate demographic, clinical, and ocular features of patients with sarcoidosis. Methods : The study involved 47 biopsy-proven sarcoidosis patients. Patients were divided into 2 groups; group 1 had uveitis and group 2 had no uveitis. Demographic and clinical features of groups were compared. Ocular manifestations in group 1 were also evaluated. Results : Twenty-six patients (53.3%) had uveitis. The incidence of uveitis was more frequent between ages 21 and 40. The most frequent type of uveitis was intermediate uveitis (46.1%), followed by panuveitis (38.4%) and anterior uveitis (15.3%). The incidence of advanced pulmonary disease was significantly higher in patients with uveitis. Conclusions : Intermediate uveitis was the most frequent type of uveitis noted in our series of patients with sarcoidosis.